Influence of the growing area on oil palm (Elaeis guineensis) inflorescences insects population - Hervé, Koua Kouakou; Moise, Akpesse Apka Alexandre; Yalamoussa, Tuo; N’klo, Hala (Journal of Research in Biology, 2013)
Oil palm tree grows naturally on low ground and on plain. Seed production varies from one area to another on the same oil palm plantation. Pollination of oil palm is essentially entomophilous; it appeared useful to assess the influence of the growing area on the fluctuation of pollinating insects’ population. Samplings were performed each month on male and female inflorescences during two years on plots in lowland and plain. The insects showed no qualitative change from one area to another. Sixteen species of insects were observed on the male inflorescences against 10 species on female inflorescences. The inflorescences showed variation in the number of insects based on the growing area and the stage of flowering.